Pengaruh Pendapatan Asli Daerah dan Transfer ke Daerah Dana Desa Terhadap Kemandirian Keuangan Daerah Kabupaten/Kota di Provinsi Riau The Effect of Regional Original Income and Transfers to Village Fund Areas on Regency/City Regional Financial Independenc - Ratnaningtyas, Endah Marendah; Kurniawan, Andre; Sujoko, Sujoko; Fathona, Citra Amira Putri (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2023)
This study aims to determine whether green products, green brands, and green advertising have a significant effect on the purchase decision of Lemonilo Noodles. The variables of this study are green product, green brand, green adversiting as an independent variable and purchasing decision as an independent variable. The sampling technique uses a nonprobability sampling technique of purposive sampling type with a sample of 100 respondents. The population in this study is consumers of Lemonilo Noodle products among students of the Special Region of Yogyakarta. The research method used is quantitative research method. The results of this study are as follows: Green product, Green brand, and Green advertising together have a significant effect on purchasingdecisions.